Relationship between severe obesity and gut inflammation in children: what's next? - Assante Luca; Squeglia Veronica; Franzese Adriana; Caiazzo Maria; Cicalese Maria; Spagnuolo Maria; Valerio Giuliana; Merone Rossella; Guarino Alfredo (BMC, 2010)
Abstract Background Preliminary evidence suggests an association between obesity and gut inflammation. Aims To evaluate the frequency of glucose abnormalities and their correlation with systemic and intestinal inflammation in severely obese children. Patients and Methods Thirty-four children (25 males; median age 10.8 ± 3.4 yrs) with severe obesity (BMI >95%) were screened for diabetes with oral glucose tolerance test (OGTT), systemic inflammation with C-reactive protein (CRP) and gut inflammation with rectal nitric oxide (NO) and faecal calprotectin. Results BMI ranged from 23 to 44 kg/m2, and BMI z-score between 2.08 e 4.93 (median 2.69 ± 0.53). Glucose abnormalities were documented in 71% of patients: type 2 diabetes in 29%, impaired fasting glucose (IFG) in 58%, and impaired glucose tolerance (IGT) in 37.5%. Thirty-one patients (91%) were hyperinsulinemic. CRP was increased in 73.5% with a correlation between BMI z-score and CRP (p 0.03). Faecal calprotectin was increased in 47% patients (mean 77 ± 68), and in 50% of children with abnormal glucose metabolism (mean 76 ± 68 μg/g), with a correlation with increasing BMI z-score. NO was pathological in 88%, and in 87.5% of glucose impairment (mean 6.8 ± 5 μM). Conclusions In this study, the prevalence of glucose abnormalities in obese children is higher than in other series; furthermore, a correlation is present between markers of systemic and intestinal inflammation and glucose abnormalities.